SHAREHOLDER‘S DERIVATE ACTION: EX LEGE MEASURES TO PREVENT SHAREHOLDER’S ABUSE - Mikalonienė, Lina (Teisė, 2015)
This article is the second article on the topic related to the shareholder‘s derivate action. After evaluating the key general aspects of the shareholder’s derivate action (e.g. concept, rationale and goals) with respect to the Lithuanian Corporate Law, this article analyzes some ex lege protective measures to prevent shareholder’s abuse in bringing shareholder‘s derivate action as well as evaluates need to revise the related Lithuanian legislation. The focus of the article is, first, on specific requirements for shareholder’s standing (e.g. locus standi of minority shareholders, contemporaneous ownership rule, continuing ownership rule) and, second, prior demand requirement as ex lege protective measures devoted to protect shareholders’ investment in a properly balanced way. It is concluded in the article that from the Lithuanian legislation perspectives shareholder’s locus standi for derivative action should be vested to each shareholder having legitimate interest in both public and private limited liability companies without requiring to comply with the above mentioned shareholder’s standing requirements as well as without requiring first mandatory making a demand to the company, as it is currently being established by the Lithuanian legislation. Taking into account the rare shareholder’s derivative action litigation in Lithuania, there is no need to change the Lithuanian legislation from practical point of view as well.